Synthesis of 3Z, 6Z, 9Z-Tricosatriene: A component of the sex pheromone of Neoleucinodes elegantalis - Cabrera, Aivlé; Urdaneta, Neudo (Ciencia, 1970)
A synthetic route was developed to obtain 3Z,6Z,9Z-tricosatriene from methyl linolenate. 3Z,6Z,9Z-tricosatriene is a sex pheromone component of tomato fruit borer Neoleucinodes elegantalis, which exhibits synergistic effect on the attraction of males to the lures, when tested along with the main compound 11E-hexadecen-1-ol. This triunsaturated hydrocarbon belongs to a new family of biologically active compounds recently discovered in Lepidopteran sex pheromones.